The Role Of Marketing Manager In Bridging The Gap In Contractual Agency-Client Relationship With Special Reference To Advertising In Malaysia - M., Mutiso Raphael (2009)
The researcher extend theory and empirical findings on inter-firm commitment by using a model that examines how agency behaviours (accessibility and assertiveness) and client behaviours (accessibility and indecisiveness) influence the working relationship (productive interaction and conflict) and agency performance (creative quality-implementation and agency proactivity) that, in turn, influence clent trust and commitment.